Lg(3x-7)+lg2=lg(x+3)+lg(x-3)  

Lg(3x-7)+lg2=lg(x+3)+lg(x-3)  
Гость
Ответ(ы) на вопрос:
Гость
 ОДЗ: 3x-7>0 , x>-7/3            |             x+3>0, x>-3               |    x>3              x-3>0, x>3                |      lg(3x-7)+lg2=lg(x+3)+lg(x-3)                                 lg((3x-7)*2)=lg((x+3)(x-3))                                       lg(6х-14)=lg(x^2-9)                                                     6x-14=  x^2-9  x^2+6x+5=0 x=-1               x=-5 рівняння розвязків немає  
Не нашли ответ?
Ответить на вопрос
Похожие вопросы